Assessing Water Quality by Statistical Methods - Barbulescu, Alina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Human society's progress has increased the quantity of pollutants emitted into the environment. Water is one of the natural resources most affected by economic activity, with pollutants reaching water bodies without proper treatment. In this context, this book presents the latest advances and developments in statistical approaches for evaluating and forecasting water resources quality. New methodologies for analyzing and predicting the water quality that can be applied in related fields are also presented.